Sur les « expressions macaroniques » de la critique d’art de Théophile Gautier (dialogue entre peinture et littérature) - Benda, Mihály (Verbum – Analecta Neolatina, 2009)
Théophile Gautier used the arts as major references in his writings. This paper brings to light which artistic values are handled by his critical reviews and for what purpose. We will reassess the notion of transposition d’art, and highlight the differences between works of art and poems.